THE EFFECTIVENESS OF THE USE OF GROWTH REGULATORS IN THE CULTIVATION OF WINTER WHEAT DEPENDING ON AGROMETEOROLOGICAL INDICATORS - Ласло, Оксана; Олепір, Роман (SWorldJournal, 2024)
The paper considers the question of the effectiveness of the use of plant growth regulators in the cultivation of winter wheat under late sowing periods and weather and climate conditions. The research of scientists on the issue of the positive influence